Actualization Of Parenting and Teacher Collaboration in Instilling the Character of Early Childhood Responsibility - Rizka Latifa (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
This study aims to analyze more deeply about the actualization of parenting collaboration between parents and teachers in instilling the character of responsibility in children. A phenomenological approach was utilized to delve into the perspectives of the participants involved. Data were analyzed using the model proposed by Milles, Huberman, and Saldana, encompassing data collection, data condensation, data presentation, and drawing conclusions. The research findings indicate that collaboration between parents and teachers in instilling a sense of responsibility in early childhood can create an environment conducive to the formation of responsible values in children. Through close cooperation, children can comprehend the importance of being accountable for their actions and decisions, with parents serving as primary role models at home and teachers reinforcing these values in the school environment. Keywords: parent and teacher collaboration, character education parenting, responsibility, early childhood